Perinatal hypoxic-ischemic brain injury in large animal models: Relevance to human neonatal encephalopathy - Koehler, Raymond C (J Cereb Blood Flow Metab, 2018)
Perinatal hypoxia-ischemia resulting in death or lifelong disabilities remains a major clinical disorder. Neonatal models of hypoxia-ischemia in rodents have enhanced our understanding of cellular mechanisms of neural injury in developing brain, but have limitations in simulating the range, accuracy, and physiology of clinical hypoxia-ischemia and the relevant systems neuropathology that contribute to the human brain injury pattern. Large animal models of perinatal hypoxia-ischemia, such as partial or complete asphyxia at the time of delivery of fetal monkeys, umbilical cord occlusion and cerebral hypoperfusion at different stages of gestation in fetal sheep, and severe hypoxia and hypoperfusion in newborn piglets, have largely overcome these limitations. In monkey, complete asphyxia produces preferential injury to cerebellum and primary sensory nuclei in brainstem and thalamus, whereas partial asphyxia produces preferential injury to somatosensory and motor cortex, basal ganglia, and thalamus. Mid-gestational fetal sheep provide a valuable model for studying vulnerability of progenitor oligodendrocytes. Hypoxia followed by asphyxia in newborn piglets replicates the systems injury seen in term newborns. Efficacy of post-insult hypothermia in animal models led to the success of clinical trials in term human neonates. Large animal models are now being used to explore adjunct therapy to augment hypothermic neuroprotection.